FT-IR spectra and vibrational spectroscopy of Andrographolide. Issue 5 (2006) - Singh Singh, P. K. P. K.; Hasan Hasan, Tanveer Tanveer; Prasad Prasad, Onkar Onkar; Sinha Sinha, Leena Leena; Raj Raj, Kanwal Kanwal; Misra Misra, Neeraj Neeraj
Abstract : A complete normal coordinate analysis was performed for andrographolide in terms of the calculation by using Wilson's G-F matrix method and Urey Bradley force field. Normal coordinate analysis has been carried out to understand the dynamical behaviour of the bioactive labdane diterpenoid of the medicinally useful terrestrial plant Andrographis paniculata. The structural elucidation of a novel, biologically active natural product followed by its total synthesis lays the groundwork for investigations into its biological mechanism of action including putative cellular receptor isolation.